TRADITIONAL VERSUS CYBER WORKPLACE BULLYING: MECHANISMS LEADING TO EMPLOYEE BURNOUT - Battulga, Altantsetseg; Rentsendorj, Munkhtuya (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
Workplace bullying is a common psychosocial stressor in modern organizational settings, significantly undermining employee well-being, job performance, and overall organizational effectiveness. In-person bullying typically involves frequent, negative behaviors from colleagues or supervisors, such as neglect, belittlement, and verbal abuse, whereas cyberbullying occurs through digital communication channels, targeting employees’ reputation, personal space, and social interactions. This study investigates the direct effects of both in-person and cyberbullying on employee disengagement using data from 150 employees in Mongolian business organizations. Results indicate that both forms of bullying increase psychological exhaustion, thereby intensifying disengagement. These findings offer theoretically informed guidance for organizational practice, emphasizing the need to detect and prevent workplace bullying and to implement policies that protect employees’ psychological well-being.